Persepsi Masyarakat Karo Terhadap Kesetaraan Gender (Studi Kasus di Desa Jandi Meriah, Kecamatan Tiganderket, Kabupaten Karo) - Radhiah Amna; Ifani Delaila; Lia Rismawati; Rafiqah Amalia; Nona Zanuwariska Dalimunthe; Nurhidayanti Sitorus (CV. Ulil Albab Corp, 2024)
This study aims to analyze the perceptions of the Karo community regarding gender equality in Jandi Meriah Village, Tiganderket District, Karo Regency. Using a qualitative approach, data were collected through semi-structured interviews, focus group discussions, and observations. Participants consisted of religious leaders, educators, and a diverse group of community members. The findings indicate that the majority of the community still views men as family leaders, while women are positioned as homemakers. Although formal education and religious teachings have begun to introduce the values of equality, their application in daily life remains limited by traditional norms. The younger generation demonstrates more egalitarian views; however, strong cultural influences continue to hinder the achievement of true gender equality. This study concludes that while progress has been made in understanding gender equality, greater efforts are needed to change entrenched practices and norms within the Karo community.